The Roles of Perceived Neighborhood Disorganization, Social Cohesion, and Social Control in Urban Thai Adolescents' Substance Use and Delinquency - Hilary F. Byrnes (2018)
Substance use and delinquency in Thai adolescents are growing public health concerns. Research has linked neighborhood characteristics to these outcomes, with explanations focused on neighborhood disorganization, social cohesion, and social control. This study examines the independent associations of these neighborhood constructs with Thai adolescents' substance use and delinquency, through peer deviance, to determine which neighborhood aspects are particularly important. Families (N = 420) with adolescents aged 13 to 14 were randomly selected from 7 districts in Bangkok, Thailand. Structural equation modeling showed that adolescents', but not parents', perceptions of greater disorganization were related to increased rates of both minor and serious delinquency. Surprisingly, greater neighborhood cohesion was related to greater minor delinquency. Peer deviance was unrelated to neighborhood variables. Findings can inform prevention strategies for Thai adolescents, as results suggest that neighborhoods are important for adolescent behaviors regardless of culture. Further work should help communities make use of social cohesion to benefit residents. © The Author(s) 2011.